Determinants of zakat compliance behaviour: a case of Lembaga Zakat Selangor / Noriham Shaari, Nur Aida Syabiha Mamat Asri and Zatul ‘Ain A’isyah Takiyuddin - Shaari, Noriham (2022)
The main purpose of this research is to study on the determinants of zakat compliance behaviour among zakat payers at Lembaga Zakat Selangor. Moreover, this study is to examine the relationship between attitude, subjective norms and Islamic knowledge and zakat compliance behaviour. Data was collected through a survey of 384 respondents using the approach of quantitative research methods. Analysis of the quantitative data revealed that attitude, subjective norms and Islamic knowledge are significantly associated with zakat compliance behaviour. Of all the independent variables, subjective norms is most significantly associated with zakat compliance behaviour among zakat payers at Lembaga Zakat Selangor. Although this research does not support general conclusions, the significant relationship between attitude, subjective norms and Islamic knowledge and zakat compliance behaviour among zakat payers might be replicated elsewhere.